The Use of Trigger Words in the Modern Political Post-Soviet Discourse of the Russian-Speaking and English-Speaking Press (Using the Example of Publications Kommersant, Izvestia, The Guardian, The Independent, The New York Times and The Washington Post) - Victorovna, Martynenko Elena; Olegovna, Popova Elena; Kimovich, Malakhovskiy Aleksey; Alekseevna, Ivanova Alina; Andreevna, Melnichenko Angelina (Journal of Ecohumanism, 2024)
In the article, the authors dwell on trigger words as special words (usually used by journalists intentionally) that evoke a certain associative chain and evaluation of the object in the reader's mind. In the theoretical part of the study, they consider different interpretations and definitions of this phenomenon by other researchers. In the practical part of the study, the authors analyzed 800 articles from Russian (Kommersant and Izvestia), British (The Guardian and The Independent) and American (The New York Times and The Washington Post) articles, where the authors of the articles use trigger words when covering modern political post-Soviet discourse. The authors analyze the trigger words used, identifying triggers-characters, trigger-symbols and trigger-significant phenomena. As results of the study, the authors of the article provide graphs that clearly show the ratio of certain trigger words in the media of different countries. The study was carried out within the framework of the initiative research work of the Theory and History of Journalism Department of the philological faculty of the RUDN University № 050737-2-000 “Research of media systems and the media industry in Russia and the world: a scientific and educational component”.